The Internalization of the Pancasila and Rahmatan Lil Alamin Student Profiles Dimensions in the Implementation of the Merdeka Curriculum - Cahyanto, Bagus; Badaruddin, Sukri; Kamarzaman, Mohd Haidhar; Syafuddin, Ahmad; Suwandayani, Beti Istanti (IAIN Ponorogo, 2024)
Merdeka Curriculum provides great opportunities for schools to develop strategies to strengthen students' competencies, skills, and flexibility. This study explores how the practice of enhancing the dimensions of the Pancasila and Rahmatan Lil Alamin student profiles in the Merdeka curriculum at madrasa. The setting of the research was MIS Mambaul Ulum Lamongan. It was one of the schools with good practices in implementing the Merdeka curriculum. The researcher used a qualitative approach in this study to achieve this goal. The results of the study show that the strategy of strengthening the Pancasila and Rahmatan Lil Alamin student profile is carried out in an integrated manner through various approaches. All dimensions are integrated into intracurricular, co-curricular learning, madrasah programs, and extracurricular activities. On the other hand, madrasahs also manage the school environment and increase parental involvement to support the achievement of Profil Pelajar Pancasila dan Rahmatan Lil 'Alamin (P3RA). These findings can contribute to future madrasas' educational policies, especially in strengthening the P3RA dimension sustainably.